Approximate function for unsteady aerodynamic kernel function of aeroelastic lifting surfaces - Sulaeman, Erwin; Ahmed, Layeeq (IIUM Press, 2014)
Prediction of unsteady aerodynamic loads is still the most challenging tasks in flutter aeroelastic analysis. Generally, the numerical estimation of steady and unsteady aerodynamics of thin lifting surface is conducted based on an integral equation relating aerodynamic pressure and normal wash velocity. The present work attempts to increase the accuracy of the prediction by using an approximate approach to evaluate kernel function occurring in the integral equation in the form of cylindrical function. Following previous approximation approaches by other researchers to solve the cylindrical function for planar lifting surfaces, this paper extends such approaches to non planar lifting surfaces. To increase the accuracy of the method, the integration region of the kernel function is divided into two parts – near and far regions, where a nonlinear regression curve fitting technique is adapted to estimate the denominator part of the cylindrical function of each region